The Cost of Sustainability: Energy Transition in Light of Business and Human Rights and ESG Frameworks - Gorini Gamba, João Roberto; Ruy Cardia Atchabahian, Ana Cláudia (Homa Publica - Revista Internacional de Derechos Humanos y Empresas, 2024)
This paper aims to understand cost involving the process of energy transition to a more sustainable planet considering Business and Human Rights and ESG frameworks, since this transition is driven by the urgent need to address the irreversible impacts of climate change, requiring international society and States to adapt to new realities. A major negative aspect of developing clean and sustainable energy is the increasing reliance on minerals often extracted in Global South States, marked by economic, social, and cultural disparities, and non-democratic structures. These conditions frequently lead to human rights violations, as highlighted in recent reports on illegal mining in Myanmar. The Non-Governmental Organization Global Witness reported serious human rights and environmental abuses in Myanmar, where rare minerals are extracted for EVs and wind turbines. These violations have been exacerbated by the political instability following the 2021 military coup. This work critically examines how energy transition dynamics must be redesigned to avoid replicating exploitative practices commonly seen in the Global North-South corporate dynamics. It emphasizes, on this regard, the need for these processes to support, rather than undermine, democratic and human rights standards. The analysis draws on several references: BHR frameworks, ESG corporate practices, academic research on human rights violations in supply chains, TWAIL literature, and academic considerations on the role of democracy in human rights protection and its close connection to sustainability in a broad sense.